Secondary School Teachers ’ Understanding of Gender - Responsive Pedagogy in Bridging Inequalities of Students ’ Learning in Tanzania - Mhewa, Mariana Manyus; Bhalalusesa, Eustella Peter; Kafanabo, Eugenia (Papers in Education and Development, 2021)
Abstract This study examined secondary school teachers ' understanding of gender responsive pedagogy as an approach to enhance equitable students ' participation in learning. A convergent parallel mixed research design was adopted with convenience and stratified purposive sampling techniques in which 146 secondary school teachers from Monduli district and Mbulu town councils in Tanzania were involved. Questionnaire and interview schedules were used to collect quantitative and qualitative data respectively. The Statistical Package for Social Sciences was then used for descriptive analysis, while thematic content analysis technique was used to make sense of qualitative data. Findings revealed that secondary school teachers have limited knowledge on gender responsive pedagogy as an approach for equitable students ' participation in learning which is partly attributed to limited gender content mainstreamed in teacher education. Keywords: gender, inequality, participation in learning, pedagogy